PELAKSANAAN PARTISIPASI MASYARAKAT DALAM PEMBAGUNAN FISIK DESA DI SURYA INDAH KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Sawitri Sawitri; Lilis Suriani (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This thesis entitled "the implementation of community participation in physical development in the beautiful solar village subdistrict pangkalan kuras district pelalawan" by Sawitri. This thesis aims to find out the implementation of organizing community participation in rural development whether it is running well or not and know the involvement of the community in maintaining the results of development and evaluate of the development program that has been realized and what has not been realized whether the assessment of villagers with the results of development. This problem is discussed based on facts in the field using quantitative research methods and then combined with descriptive qualitative research methods. The results of the research that has been conducted have shown that the participation of the beautiful solar villagers in planning, implementation, utilization, and development evaluation is quite good in its presentation. Public awareness of the importance of village development has been quite maximal. In this study, the inhibiting factor is discussed about the education of rural communities which is still minimal for the level of progress if measured for now. This good participation is also the responsibility and duty of village government and village communities to always strive in promoting and enhancing community participation. It also requires the attention especially the government to motivate, invite and try to increase community participation in physical development of the village.